Nostalgia w poezji Stanisława Barańczaka - Rydz, Agnieszka (Studia Rossica Posnaniensia, 2019)
The article Nostalgia in Stanisław Barańczak’s Poetry was inspired by Douwe Draaisma’s essay, a Dutch psychology theoretician, The Fabric of Nostalgia. About the Phenomenon of Mature Memory’s Age (2010). This model of nostalgia is based on the psychological phenomenon of memory reminiscence. The article presents the evolution of theme of nostalgia in Barańczak’s poetry.